FAKTOR?FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PERDARAHAN POSTPARTUM - Siti Aisyah (Poltekkes Kemenkes Medan, 2022)
Postpartum hemorrhage is bleeding more than 500-600 ml for 24 hours after the child is born (Mochtar, 2015). Based on the time of occurrence of postpartum hemorrhage can be divided into primary bleeding and secondary bleeding. Postpartum hemorrhage is the most common cause of all deaths from obstetric hemorrhage. Postpartum hemorrhage is bleeding that exceeds 500 ml after the baby is born with vaginal delivery and exceeds 1000 ml at cesarean section (Chunningham, 2012). The sample in this study was 90 people using a systematic random sampling technique. From the results of the analysis, it is known that there is a relationship between uterine atony (p-value 0.029), retained placenta (p-value 0.002), and multiple pregnancies (p-value 0.007), with the incidence of postpartum hemorrhage. In 2020. It is recommended to be an input for the health services that have been provided to improve the quality of services to maternity mothers, especially those experiencing postpartum hemorrhage.